2004
DOI: 10.1002/fld.722
|View full text |Cite
|
Sign up to set email alerts
|

A combined analytical–numerical method for treating corner singularities in viscous flow predictions

Abstract: SUMMARYA combined analytical-numerical method based on a matching asymptotic algorithm is proposed for treating angular (sharp corner or wedge) singularities in the numerical solution of the Navier-Stokes equations. We adopt an asymptotic solution for the local ow around the angular points based on the Stokes ow approximation and a numerical solution for the global ow outside the singular regions using a ÿnite-volume method. The coe cients involved in the analytical solution are iteratively updated by matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…The asymptotics can be matched with the numerical solution outside a given radius in a variety of ways. This approach has proved successful in similar situations in which corner singularities exist [34]. However, it has been found that for our problem such an alteration of the scheme merely shifts the pressure cliff to the arc at the radius where the asymptotics has been applied.…”
Section: Remedies Described In the Literaturementioning
confidence: 94%
“…The asymptotics can be matched with the numerical solution outside a given radius in a variety of ways. This approach has proved successful in similar situations in which corner singularities exist [34]. However, it has been found that for our problem such an alteration of the scheme merely shifts the pressure cliff to the arc at the radius where the asymptotics has been applied.…”
Section: Remedies Described In the Literaturementioning
confidence: 94%
“…Blum [6] discussed application of dual singular function method to semilinear biharmonic equations, such as the Navier-Stokes equations or the von Kármán equations, however, presenting the numerical results only for linear problems. Shi et al proposed a method that combines asymptotics of the solution and local mesh refinement near a corner for solution of the Navier-Stokes equations [34]. The authors of [34] mentioned using a local block mesh refinement, which seems to be equivalent to algebraic mesh refinement.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al proposed a method that combines asymptotics of the solution and local mesh refinement near a corner for solution of the Navier-Stokes equations [34]. The authors of [34] mentioned using a local block mesh refinement, which seems to be equivalent to algebraic mesh refinement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods range from special mesh-reÿnement schemes to sophisticated techniques that incorporate, directly or indirectly, the form of the local asymptotic expansion, which is known in many occasions. An exhaustive survey of treatment of singularities in elliptic boundary value problems is provided in the recent articles by Li and Lu [1], Dosiyev [2] and Shi et al [3]. Knowledge of the coe cients appearing in the local solution expansion is often desired in many engineering applications.…”
Section: Introductionmentioning
confidence: 99%